Promethazine-HCl Determination Using Entrapped Persulphate in Water Crystals by Flow Injection / Stopped - Flow Technique and Ayah 3SX3-3D Solar Cell Micro Photometer - M. A. Shakir, Issam (Iraqi Journal of Science, 2023)
A new mode of methodology was adopted in the assay of PM- HCL based on the use of water crystal gel bead made of poly acrylic acid in which the gel beads were left to absorbe persulphate solution that is necessary for the oxidation of PM- HCL in aqua media . The water crystal act as a reserviour for S2O82- . Optimum parameters were studied giving to specify the chemical and physical parameters. Two line manifold was used .The flow rates of 1.5 and 1.2 ml.min-1 was used , 3 gel beads , 120 μL sample volume , a linear dynamic range extend from 0.01- 18 mmol.L-1. A correlation coefficient (r) of 0.9991while the percentage linearity (r2%) of 99.82% with R.S.D% at 8 mmol.L-1 promethazine-HCl is less than 0.5% (ten replicates) and a detection limit (S/N=3) of 19.25 ng/sample was obtained . Throughput of 20 sample.hr-1 can be measured. A successful application on available drug in the market was assayed. A complete satisfactory result was obtained .Using t-test it was shown that there was no significant difference between the Practical value and the quoted value, on that basis the new method can be accepted as an alternative analytical method.